EXPANDING GRADUATE ACCOUNTING WITH ONLINE TOOLS - Page, James Kyle (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2018)
In this paper, the author examines the technology needs of graduate accounting students and discuss research on the interaction between technology and the graduate level accounting course. Using the features of online tools and specialized teaching methods can be offered to graduate accounting students. An important component is the use of online tools and digital literacy skills to fill the gaps of graduate students who may not be proficient in the use of technology. The purpose of this study was to examine the traditional approach to teaching graduate accounting with textbook only in comparison to teaching with the use of online tools. The aim was to introduce students to the use of online tools and how it could be used to enhance their twenty-first-century skills. The primary goal of the study was to determine whether the treatment group learned more than the control group taught in the previous semester the non-traditional approach. In conclusion, the use of online tools alone is not enough to result in enhancing twenty-first-century skills. The study indicated that teaching graduate accounting should include every effective resource at the disposal of the instructor.